1979
DOI: 10.1172/jci109617
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Liver in Regulation of Ketone Body Production during Sepsis

Abstract: A B S T R A C T During caloric deprivation, the septic host may fail to develop ketonemia as an adaptation to starvation. Because the plasma ketone body concentration is a function of the ratio of hepatic production and peripheral usage, a pneumococcal sepsis model was used in rats to measure the complex metabolic events that could account for this failure, including the effects of infection on lipolysis and esterification in adipose tissue, fatty acid transport in plasma and the rates of hepatic ketogenesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…These data suggest that the decrease in these nuclear hormone receptors and their coactivators plays an important role in regulating FA metabolism during infection. In fact, studies have shown that, during sepsis, there is a decrease in FA oxidation in the liver, kidney, and heart ( 24,(27)(28)(29)(30)(31)(32).…”
Section: Isolation Of Rna and Quantitative Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that the decrease in these nuclear hormone receptors and their coactivators plays an important role in regulating FA metabolism during infection. In fact, studies have shown that, during sepsis, there is a decrease in FA oxidation in the liver, kidney, and heart ( 24,(27)(28)(29)(30)(31)(32).…”
Section: Isolation Of Rna and Quantitative Real-time Pcrmentioning
confidence: 99%
“…This increase appears to be substrate driven as expression of the enzymes that catalyze the incorporation of FAs into triglycerides is decreased rather than increased. Thus, in the diaphragm, similar to the liver, heart, and kidney, infection induces a decrease in FA oxidation with an increase in FA incorporation into triglycerides ( 24,(27)(28)(29)(30)(31)(32).…”
Section: Effect Of Lps Treatment On Nuclear Hormone Receptor Coactivamentioning
confidence: 99%
“…In animal models, it was demonstrated that E. coli-induced sepsis resulted in a significant decrease in lipoprotein lipase (LPL), leading to a marked decrease in clearance of triglycerides and free fatty acids in cardiac tissue, adipose tissue, and muscle (64,65). This was associated with an increase in de novo hepatic lipogenesis (65,131). The administration of LPS and many cytokines to animals rapidly increased serum triglyceride levels which persisted (65).…”
Section: Obesity and Sepsismentioning
confidence: 99%
“…In general, nonesterified fatty acid concentration in blood decreases during sepsis in man and in experimental animals. Wannemacher et al (19) reported that the decrease could be a consequence of an infection-induced decrease in plasma albumin, which is the fatty acid carrier. The albumin-bound free fatty acids are only one source of oxidizable fatty acid substrates for peripheral tissues (23).…”
Section: Discussionmentioning
confidence: 99%